The Use of Volunteers in Local Study Library Projects: A Case Study of the Walter Gardiner Photography Project - Hewitt, Beth; Eve, Juliet (Evidence Based Library and Information Practice, 2012)
Abstract Objectives – Interviews with library staff and volunteers were conducted to evaluate the use of volunteers in UK public libraries via a case study of the Walter Gardiner Photographic Project, a digitisation project based in Worthing Library, to inform future guidelines on volunteer usage and to make recommendations to existing practice. Methods – Fourteen semi-structured interviews were carried out to explore the perceptions and experiences of both staff and volunteers of the project. All interviews were fully transcribed and then coded to identify emergent themes. Results – Key positives for volunteers were professional training, good time management and organization by staff, the friendliness and approachability of staff, and the informal nature of the volunteering. Enjoyment of the work and forming close relationships with others were key motivating factors. For staff, the completion of work which would have otherwise been impossible was the most positive outcome. Problem areas identified by volunteers were lack of contact time with project staff and feeling isolated from other library staff. For project staff, a lack of professionalism on behalf of some volunteers was the primary negative. Key issues to emerge were the need to strike a balance between formal and informal management, the need for good integration between the volunteers and host organization, and the importance of acknowledging the nature of the voluntary commitment. Conclusions – The project proved overall to be a successful example of using volunteers in public library projects with good examples of volunteer recruitment, training, and management being demonstrated. Areas of conflict that did arise stemmed from differing expectations of levels of service between staff and volunteers. Clarification on these expectations through a written volunteer agreement is advocated for further projects.